Digital transformation of internal audit in Kazakhstan - Satybaldiev, Zh.Sh.; Yerdavletova, F.K.; Nurmagambetova, A.Z.; Niyazbekova, Sh. (Journal of Economic Research & Business Administration, 2025)
In the context of the accelerating digital transformation of the Republic of Kazakhstan’s economy, the need to rethink the role of internal audit and the tools for modernizing production systems is becoming increasingly important, particularly in the small and medium-sized enterprise (SME) sector. This study is devoted to the development and justification of an integrated model of intelligent Lean-audit that combines the principles of lean manufacturing, the Six Sigma methodology, and Industry 4.0 concepts. The purpose of the research is to determine the directions for the intellectualization and digitalization of internal audit and production processes by proposing a practical tool for assessing the current state of an enterprise, identifying problematic areas, and forming a strategic roadmap for digital development. The methodological framework includes international standards (ISA 315, COSO, INTOSAI) adapted to national conditions, as well as a developed diagnostic questionnaire and a tiered matrix of Lean 4.0 methods. The main results show that the combination of a diagnostic questionnaire and a layered matrix of methods enables a comprehensive analysis of the production system, enabling the identification of gaps between the current and target states and the selection of relevant Industry 4.0 tools. The developed Lean 4.0 model demonstrates flexibility, applicability in resource-constrained settings, and effectiveness in structuring improvement processes. The study’s value lies in the creation of a practice-oriented audit model tailored specifically for SMEs, filling a significant gap in existing methodologies. Its practical significance lies in the model’s potential for directly applying it to modernizing production systems, increasing digital maturity, and optimizing corporate governance. The transformation of internal audit is becoming a strategic foundation for a sustainable and transparent economy in Kazakhstan: the use of digital technologies and AI creates an intelligent control system focused on risk prevention, increasing trust, and supporting long-term development. Key words: internal audit, digital transformation, Lean 4.0, Industry 4.0, Six Sigma, Big Data.